Women Principals in Education: A Literatur Review on Leadership, Gender, and Empowerment - Kartiwi, Asti Putri; Sary, Fetty Poerwita; Hadipassa, Emal (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2025)
Publications on the topic of women's leadership have grown rapidly since gender equality became a strategic issue worldwide. The aim of this publication is to map publication trends on the topic of women's leadership, including authors who write extensively on the topic, organizations involved in the publication, and publication trends from year to year. The method used is bibliometric analysis using VosViewer. The data used is from the Scopus database with the search keyword “women's leadership,” yielding 74,046 documents, consisting of 54,288 journal articles, 6,582 book chapters, 4,747 reviews, 3,568 conference proceedings, 2,497 books, 1,046 notes, 707 editorials, 311 short surveys, 164 letters, 70 errata, 32 conference reviews, 26 retracted publications, and 6 data papers. The results of the analysis show that publication trends from 1980 to 2024 have continued to increase significantly. The two authors with the most publications are not primarily focused on the social sciences. Two institutions have the highest number of publications on “women's leadership in education,” namely the University of Alabama and Northwestern University. Authors from these two universities are known to have collaborated on publications. Further recommendations suggest that publications on the “women's leadership in education” theme can be developed into empirical research, particularly by connecting it to other fields of study.